Assessment of the challenges influencing the adoption of smart building technologies - Baharetha, Saleh; Soliman, Ashraf M.; Hassanain, Mohammad A.; Alshibani, Adel; Ezz, Mohamed Salah (Frontiers in Built Environment, 2024)
Over the past few decades, the Smart Building Projects have received increasing attention. There has been a large number of studies done to define smart building technologies (SBT) globally, identify the challenges it faces, identify areas where it needs to be improved, etc. This study aimed to examine the concept and terminology of SBT as well as the expertise and experience of those participating in SBP in the Arab Gulf countries like Saudi Arabia. This study explored the challenges, that SBT would experience during its life cycle. The challenges were divided into four broad categories: (Programming and Feasibility analysis phase, Design phase, Installation and Commissioning phase-Operation and Maintenance phase).A mixed approach of literature review, pilot-testing and questionnaire survey was utilized to identify and assess the challenges affecting the adoption of smart building technologies. Fifty-five challenges were identified and categorized under four groups, corresponding to the key phases of the project life cycle. The pilot tested questionnaire survey was conducted on a targeted sample of (90) Architects/Engineers, Managers, and Contractor's practitioners in big cities like Riyadh City. This research expands the body of knowledge, through providing AEC/FM practitioners, with the influential challenges on the adoption of SBT.